Main theoretical approaches to a concept evolution research international security - Shamraeva, Valentina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
A lot of scientific papers are devoted to the issue of international security. At the same time, there are almost no works devoted precisely to the tools of the methodology of studying the concept of international security at the present stage of evolution in the scientific discussions, that greatly reduces the effectiveness of the research process. The subject matter of the article is selection of the main theoretical approaches to the study of the evolution of the concept of ‘international security’. The goal is to analyze the latest approaches to the evolution of the concept of ‘international security’ and the methodology of its study in the modern international political science. The objective is to study the main stages of the evolution of the flagship theoretical approaches to the definition of international security and the methodology of its study. Common scientific methods are used: the historical approach – in identifying the main stages of the development of the concept of ‘international security’ in the political science, generalization and retrospective analysis – in the study of the methodology of this concept in modern political science. The following results are obtained: general methodological approaches to the definition and study of international security are summarized, the main principles of its system formation, models and mechanisms of provision are outlined. The newest methodical approaches to the scientific analysis of this concept are analyzed. The author specifically discloses the modern threats that have arisen in the conditions of security at global and regional levels and that are caused by the planetary problems of the international political process, such as globalization processes, global humanity problems, transnational terrorism, etc. Conclusions: there is a large number of new theoretical trends that enter into controversy with the classical ones concerning the possibilities and methodology of knowledge of contemporary challenges of international security in modern political science of international relations. At the same time, the analyzed approaches determine the current understanding, the content and essence of international security in all its manifestations from the formation of the national interests of individual states in this area to the practical mechanisms of the functioning of the global system of international security. The effective functioning of the collective security mechanism is an integral part of international security. This problem is extremely relevant and can become the subject of separate expert discussions and studies in the field of international relations.